Factors affecting consumers' acceptance of e-commerce consumer credit service. (June 2018) - Jia, Lin; Xue, Geng; Fu, Yuwei; Xu, Longjia
Highlights: Fourteen promotion activities of Ant Check Later are summarized. Bonus, quota lifting, and scenario enrichment are extracted from these activities. Quota lifting and scenario enrichment promote users to continue using the service. Bonus and scenario enrichment foster non-users' intention to use the service. Scenario enrichment is the most important factor among the three factors.